The benefits of the earlier use of sacubitril/valsartan in de novo heart failure with reduced ejection fraction patients. (28th April 2022) - Oh, Ji‐Hye; Lee, Jae‐Man; Lee, Hee‐Jung; Hwang, Jongmin; Lee, Cheol Hyun; Cho, Yun‐Kyeong; Park, Hyoung‐Seob; Yoon, Hyuck‐Jun; Chung, Jin‐Wook; Kim, Hyungseop; Nam, Chang‐Wook; Han, Seongwook; et al.
Abstract: Aims: We evaluated the clinical outcomes and trajectory of cardiac reverse remodelling according to the timing of sacubitril/valsartan (Sac/Val) use in patients with heart failure (HF) with reduced ejection fraction (HFrEF). Methods and results: Patients with de novo HFrEF who used Sac/Val between June 2017 and October 2019 were retrospectively enrolled. Patients were grouped into the earlier use group (initiation of Sac/Val < 3 months after the first HFrEF diagnosis) and the later use group (initiation of Sac/Val ≥ 3 months after the first HFrEF diagnosis). Primary outcome was a composite of HF hospitalization and cardiac death. Secondary outcomes were HF hospitalization, cardiac death, all‐cause death, significant ventricular arrhythmia (ventricular tachycardia or ventricular fibrillation), and echocardiographic evidence of cardiac reverse remodelling including left ventricular ejection fraction (LVEF) change during follow‐up. Among 115 enrolled patients, 67 were classified in the earlier use group, and 48 were classified in the later use group. Mean period of HFrEF diagnosis to Sac/Val use was 52.1 ± 14.3 days in the earlier use group, and 201.8 ± 127.3 days in the later use group. During the median follow‐up of 721 days, primary outcome occurred in 21 patients (18.3%). The earlier use group experienced significantly fewer primary outcome than the later use group (10.4% vs. 29.2%, P = 0.010). The Kaplan–Meier survival curve showed better event‐free survival in the earlier use group than in the later use group (log rank = 0.017). There were no significant differences in cardiac death, all‐cause death, and ventricular arrhythmia between two groups (1.5% vs. 2.1%, P = 0.811; 1.5% vs. 4.2%, P = 0.375; 3.0% vs. 0%, P = 0.227, respectively). Despite a significantly lower baseline LVEF in the earlier use group (21.3 ± 6.4% vs. 24.8 ± 7.9%, P = 0.012), an early prominent increase of LVEF was noted before 6 months (35.2 ± 11.9% vs. 27.8 ± 8.8%, P = 0.007). A delayed improvement of LVEF in the later use group resulted in similar LVEF at last follow‐up in both groups (40.7 ± 13.4% vs. 39.4 ± 10.9%, P = 0.686). Although the trajectory of left ventricular remodelling showed similar pattern in two groups, left atrial (LA) reverse remodelling was less prominent in the later use group during the follow‐up period (final LA volume index: 43.6 ± 14.3 mL/m 2 vs. 55.2 ± 17.1 mL/m 2, P = 0.011). Conclusions: Earlier use of Sac/Val was related with better clinical outcome and earlier left ventricular reverse remodelling. Remodelling of LA was less prominent in the later use group implying delayed response in diastolic function.